Вибрация модифицированных зубчатых передач - Попов, А. П.; Кипреев, Ю. Н. (НТУ "ХПИ", 2012)
Выполнен сравнительный анализ уровней вибрационной активности движущегося контакта пар зубьев нормального прямозубого зацепления с модификациями "глубокого" профиля и зацепления колес с двумя и более смещенными венцами. Показано, что более эффективными возможностями для снижения уровней вибрации обладают передачи с зацеплениями колес со смещенными относительно друг друга венцами

Comparative analysis of level vibration activity of the moving contact of teeth pairs of the normal spur tooth system with modification of "deep" profile with two and more displaced too thing has been carried out. It has been shown that effective possibilities for covering vibration levels have gearings with tooth system of gears with displaced relatively each other too thing
Keywords: вибрационная активность; движущийся контакт; прямозубое зацепление; смещенные венцы; vibration activity; moving contact; effective possibilities; tooth system of gears